On economic inequality and social welfare - Begović Boris (Anali Pravnog Fakulteta u Beogradu, 2015)
The aim of the paper is to explore the relations between economic inequality and social welfare staring from the assumption that causality goes from economic inequality to social welfare. Standard methodological framework of economic science was enhanced with interpersonal function of individual welfare so the effects of economic inequality of the level of social welfare can be considered. It was demonstrated that there is no unequivocal theoretical conclusion and that differences in the preferences among people should be empirical considered for more insights. The analysis of the consequences of economic inequality to economic growth, i.e. dynamics of social welfare, demonstrated that there are numerous mechanisms of causality with the countervailing effects. The most important mechanism by which inequality speeds-up economic growth is based on the increased saving and invents rates, and the most important mechanism by which it slows-down growth is based on decreasing investments in human capital. Accordingly, there is no unequivocal theoretical conclusion also in this case. Nonetheless, modern growth theory has demonstrated that that the most dangerous economic growth is inequality of the treatment of economic agents, i.e. discrimination and exclusion, as that kind of inequality creates substantial allocative inefficiency.